Dislocation of polyfocal full-optics accommodative intraocular lens after neodymium-doped yttrium aluminum garnet capsulotomy in vitrectomized eye - Kyung Tae Kang; Yu Cheol Kim (Indian Journal of Ophthalmology, 2013)
We report a case of dislocation of WIOL-CF® polyfocal full-optics intraocular lens (IOL) after neodymium-doped yttrium aluminum garnet (Nd: YAG) laser capsulotomy in the vitrectomized eye. At 22 months before the dislocation of the IOL, a 55-year-old male patient underwent phacoemulsification with WIOL-CF® IOL implantation in a local clinic and 10 months after the cataract surgery the patient underwent pars plana vitrectomy, endolaser photocoagulation and 14% C 3 F 8 gas tamponade for the treatment of rhegmatogenous retinal detachment. At 9 months after the vitrectomy, the patient visited our clinic for a sudden decrease of vision after Nd: YAG capsulotomy in the local clinic. On fundus examination, the dislocated IOL was identified and the Nd: YAG capsulotomy site and the larger break, which is suspected to have been a route of the dislocation were observed in the posterior capsule.